2018
DOI: 10.1080/22201181.2018.1461323
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure measurement in obese patients: non-invasive proximal forearm versus direct intra-arterial measurements

Abstract: In obesity, accurate perioperative blood pressure measurement using upper arm, non-invasive blood pressure (NIBP) is technically challenging. Proximal forearm NIBP may be an acceptable substitute. Mean arterial blood pressures (MAP) estimated by proximal forearm NIBP were compared with direct intra-arterial measurements. It was hypothesised that the measurement techniques would be interchangeable if between-technique MAP differed ≤ 20% and MAP ratios were < 1.2 and > 0.8. Method: A total of 30 adults with body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Respondents in our study identified cuff placement on the forearm or leg as a clinical workaround, when placement on the arm was problematic or impossible. Studies evaluating the accuracy of forearm placement report conflicting results [ 27 , 28 , 29 , 30 ]. Recently a study evaluating intraoperative blood pressure measurements in patients with obesity suggested that NIBP measurements taken on the forearm were more accurate than those taken from the arm [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respondents in our study identified cuff placement on the forearm or leg as a clinical workaround, when placement on the arm was problematic or impossible. Studies evaluating the accuracy of forearm placement report conflicting results [ 27 , 28 , 29 , 30 ]. Recently a study evaluating intraoperative blood pressure measurements in patients with obesity suggested that NIBP measurements taken on the forearm were more accurate than those taken from the arm [ 31 ].…”
Section: Discussionmentioning
confidence: 99%